Wstęp - Marczuk-Karbownik, Magdalena; Żakowski, Karol; Agnieszka Gralak (Forms of Power in Contemporary World – Case Studies, 2023)
The introduction contains a description of the theoretical framework and the issues raised in the work, especially the categories of power.